2009
DOI: 10.1182/blood-2008-07-170316
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive localization and opposed roles of vasohibin-1 and vasohibin-2 in the regulation of angiogenesis

Abstract: We recently isolated a novel angiogenesis inhibitor, vasohibin-1, and its homologue, vasohibin-2. In this study we characterize the role of these 2 molecules in the regulation of angiogenesis. In a mouse model of subcutaneous angiogenesis, the expression of endogenous vasohibin-1 was low in proliferating ECs at the sprouting front but high in nonproliferating endothelial cells (ECs) in the termination zone. In contrast, endogenous vasohibin-2 was preferentially expressed in mononuclear cells mobilized from bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
155
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(172 citation statements)
references
References 32 publications
12
155
1
Order By: Relevance
“…Because of the similarity between VASH1 and VASH2, we examined their expression and function by the use of hypoxia-induced subcutaneous angiogenesis in mice. Our analysis revealed that VASH1 is mainly expressed in endothelial cells in the termination zone to halt angiogenesis, whereas VASH2 is mainly expressed in mononuclear cells mobilized from the bone marrow in the sprouting front to stimulate angiogenesis (16). Thus, these 2 VASH family members regulate angiogenesis perhaps in a seemingly contradictory manner.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Because of the similarity between VASH1 and VASH2, we examined their expression and function by the use of hypoxia-induced subcutaneous angiogenesis in mice. Our analysis revealed that VASH1 is mainly expressed in endothelial cells in the termination zone to halt angiogenesis, whereas VASH2 is mainly expressed in mononuclear cells mobilized from the bone marrow in the sprouting front to stimulate angiogenesis (16). Thus, these 2 VASH family members regulate angiogenesis perhaps in a seemingly contradictory manner.…”
Section: Introductionmentioning
confidence: 90%
“…We previously reported that VASH1 inhibits angiogenesis whereas VASH2 promotes it (16). We therefore examined the vasculature in the tumors and found a significant decrease in angiogenesis in tumors derived from either SKOV-3 or DISS sh-VASH2 cells (Fig.…”
Section: Knockdown Of Vash2 In Cancer Cells Decreases Tumor Growth VImentioning
confidence: 99%
See 2 more Smart Citations
“…VASH1 is located in the cytoplasm of endothelial cells and was first identified as a negative regulator of angiogenesis [2,3]. VASH2 is a homolog of VASH1, and was shown to stimulate angiogenesis in a mouse model of hypoxia-induced subcutaneous angiogenesis [3].…”
Section: Introductionmentioning
confidence: 99%